2020
DOI: 10.1021/acsami.0c15414
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Approach to Facilitate the High Filler Content in Free-Standing and Flexible Thermoelectric Polymer Composite Films Based on PVDF and Ag2Se Nanowires

Abstract: A high filler content is often needed in polymer composite-based thermoelectric (TE) films to improve their performance. Nevertheless, this often leads to poor processability and poor mechanical performance. Herein, a biomimetic approach is adopted to facilitate the filler content up to 90.5 wt % in free-standing and flexible n-type PVDF/Ag2Se TE films, where PVDF dendricolloids are a solution mixed with Ag2Se nanowires (NWs), followed by filtration. These soft dendric nanoparticles within PVDF dendricolloids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…As a result of the highest degree crystal, S 2 σ reaches 3 μW m -1 K -2 at room temperature. Another [125] reported that the best TE performance in P3HT can be achieved by doping with 17 wt% F4CNQ, attributed to the fact that the dopant at this Reproduced with permission [211] .Copyright 2018 The Royal Society of Chemistry. P3HT: Poly(3-hexylthiophene); CNTs: carbon nanotubes.…”
Section: P3htmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the highest degree crystal, S 2 σ reaches 3 μW m -1 K -2 at room temperature. Another [125] reported that the best TE performance in P3HT can be achieved by doping with 17 wt% F4CNQ, attributed to the fact that the dopant at this Reproduced with permission [211] .Copyright 2018 The Royal Society of Chemistry. P3HT: Poly(3-hexylthiophene); CNTs: carbon nanotubes.…”
Section: P3htmentioning
confidence: 99%
“…In addition to the research on F4CNQ-doped P3HT, CNT/P3HT composite materials are also in popularity [211] , from which the good performance is benefitted from the unique structure and excellent electron transport performance of CNT itself. For example, composite films with different diameters were prepared [Figure 10C].…”
Section: P3htmentioning
confidence: 99%
“…Alloy microwires are the main heating materials used in most industrial and domestic heating applications requiring high-temperature requirements [89] . These systems' advantage is that they can be readily incorporated into woven or knitted textile materials for textile applications due to wires' flexible and continuous filament nature.…”
Section: Metal or Alloy Microwiresmentioning
confidence: 99%
“…For example, Mi et al investigated the effects of excess Se on the thermoelectric properties of Ag 2 Se [23], where a maximum thermoelectric ZT of 0.85 was obtained for Ag 2 Se 1.06 . Zhou et al prepared unsupported thermoelectric films of polyvinylidene fluoride (PVDF)/Ag 2 Se via a drop coating method [24], and the maximum power factor obtained was 189.02 µW•m −1 •K −2 when the mass ratio of PVDF to Ag 2 Se was 1:9.5. Although the addition of PVDF significantly improved the flexibility and stability, it also reduced the thermal conductivity of the thermoelectric film, owing to the insulating nature of PVDF.…”
Section: Introductionmentioning
confidence: 99%